Vibrational, thermal features, and photon attenuation coefficients evaluation for TeO2-B2O3-BaO-ZnO-Na2O-Er2O3-Pr6O11 glasses as gamma-rays shielding materials - Lakshminarayana, G.; Baki, S.O.; Sayyed, M.I.; Dong, M.G.; Lira, A.; Noor, A.S.M.; Kityk, I.V.; Mahdi, M.A. (Elsevier, 2018)
Sodium zinc barium borotellurite glass systems doped with singly Er, Pr, and Er/Pr-codoped ions were fabricated via melt quenching method to study their structural, thermal, and gamma radiation shielding features. Both FTIR and Raman spectroscopic results revealed that the glass network matrix is prevailingly formed by TeO4, TeO3 + 1, TeO3, BO3 and BO4 structural clusters. The characteristic temperatures (glass transition (Tg), onset crystallization (Tx), peak crystallization (Tc), and melting (Tm)) and thermal stabilities (ΔT) were determined by differential scanning calorimetry (DSC). An increase in ‘Tg’ and (ΔT) variation within the temperature range 123–164 °C with an addition of Er2O3, Pr6O11, and Er2O3/Pr6O11 oxides indicates that synthesized glasses possess good thermal stability. For selected glasses, mass attenuation coefficient (μ/ρ) values calculated using both XCOM software and MCNP5 simulation code in the 0.015–15 MeV photon energy range were matched well. Moreover, based on the (μ/ρ) values, various shielding parameters like effective atomic number (Zeff), electron density (Ne), mean free path (MFP) and half-value layer (HVL) are evaluated. Additionally, exposure buildup factor (EBF) values have been determined using Geometric Progression (G–P) fitting method in the energy range 0.015–15 MeV and up to a penetration depth of 40 mfp, and variation of all the shielding parameters is discussed for the effect of singly Er, Pr and doubly Er/Pr ions inclusion into the host glass. As an example, the prepared rare-earth (RE)-doped glasses show lower HVL values compared to 80TeO2-20MgO and 80TeO2-20MoO3 (mol %) glasses suggesting their potentiality as good gamma radiation shielding materials.